Prognosis of T1 synovial sarcoma depends upon surgery by oncologic surgeons. Issue 4 (24th May 2016) - El Beaino, Marc; Araujo, Dejka M.; Gopalakrishnan, Vancheswaran; Lazar, Alexander J.; Lin, Patrick P.
Abstract : Background: The prognosis of early stage synovial sarcomas is not well‐defined since long‐term follow‐up is lacking in most studies. The optimal use of surgery, radiation, and chemotherapy needs to be clarified for this group. Methods: From 1994 to 2012, 63 patients were treated for localized synovial sarcoma with T1 (<5 cm) tumors. There were 27 males and 36 females. Mean follow‐up was 85 months (range 13–210). Results: At 10 years, local recurrence‐free survival was 82% (95% confidence interval [CI] 67–97%), and distant recurrence‐free survival was 95% (95%CI 89–100%). Two patients developed metastases after 10 years. Local recurrence was associated with lack of re‐excision and treatment by non‐oncologic surgeons. Microscopic residual tumor was found in 43% of re‐excised specimens. Metastasis was associated with local recurrence, tumor size ≥3 cm, and treatment by non‐oncologic surgeons. Radiation and chemotherapy treatment did not have a significant effect in this patient cohort. Conclusions: Early stage synovial sarcomas with T1 tumors have a relatively favorable prognosis but the potential for late relapse, and long‐term follow‐up beyond 10 years is recommended. Re‐excision of the tumor bed and definitive treatment by trained oncologic surgeons may decrease the risk of local recurrence and metastasis. J. Surg. Oncol. 2016;114:490–494 . © 2016 Wiley Periodicals, Inc.